FRI0053 Analysis of associations between tumor necrosis factor-alpha (TNFA -308 g>a, tnfa -238 g>a, tnfa -857 c>t) and tnf receptors (TNFRA 36 a>g, tnfrb 676 t>g) gene polymorphisms status and responsiveness to tnf-a blockers in rheumatoid arthritis. (23rd January 2014) - Swierkot, J.; Bogunia-Kubik, K.; Nowak, B.; Białowąs, K.; Korman, L.; Gębura, K.; Kolossa, K.; Jeka, S.; Wiland, P.
Abstract : Background: Despite the fact that therapy with TNF-α inhibitors constitutes a breakthrough in rheumatoid arthritis (RA) management, no improvement is still achieved in approximately 30% of casess. There is ongoing search for biochemical and clinical markers that would allow prediction of a good response to therapy with biologicals, including TNF-α inhibitors. Besides clinical factors, genetic predisposition, may be also helpful in that prediction. Objectives: The aim of the study was to evaluated whether single nucleotide polymorphisms (SNPs) within the tumour necrosis factor (TNF-α) [ TNFA -308 G>A (rs1800629), TNFA -238 G>A (rs3615525), TNFA -857 C>T (rs1799724)], and TNF receptors [ TNFR1 36 A>G (rs767455), TNFR2 676 T>G (rs1061622)] encoding genes affect the efficacy of therapy with TNF-α inhibitors in patients with RA. Methods: Genetic polymorphism was determined in 274 RA patients who had been treated with TNF-α inhibitors (adalimumab, etanercept, infliksimab, certolizumab) for at least 3 ? 6 ? months or they stop therapy because of adverse events. Outcomes were parameters of efficacy of TNF treatment and adverse events. DNA was extracted from peripheral blood taken on EDTA using Maxwell 16 Blood DNA Purification Kit (Promega Corp., Madison, WI, USA) following the recommendation of the manufacturer. Gene polymorphisms were analyzed using a polymerase chain reaction (PCR) amplification employing LightSNiP assays designed by TIB MOLBIOL GmbH, Berlin, Germany. The efficacy of therapy was evaluated according to EULAR response criteria at 3 month. Association between the relative change in DAS28 and SNP genotypes was tested by linear regression. In addition, logistic regression was applied to compare genotypes in non-responders versus, moderate and good-responders. Results: Clinical data of 274 Caucasians patients with RA treated with TNF-α inhibitors were analyzed. EULAR moderate was achieved in 69% of patients, while good EULAR response in 23% of patients at 3 months. The TNFRA GG genotype was present in 56 patients (20%), TNFRA AA in 74 patients (27%), and 144 patients (53%) were heterozygous. More patients with TNFRA AA genotype achieved a EULAR good response at 3 months compared to patients carrying the G allele (with TNFRA GG and TNFRA AG genotypes) 34%/20%/19%, respectively; p=0.011). Presence of the other polymorphism separately were not significantly associated with EULAR response at week 12. Conclusions: The TNFRA gene polymorphism was found to affect the responsiveness to TNF-α blockers in rheumatoid arthritis. The presence of the TNFRA AA genotype was associated with better response to treatment. Polymorphisms located within the TNFA promoter (-308 G>A, -238 G>A, -857 C>T) showed no association with TNF-α inhibitor related efficacy. Disclosure of Interest: J. Swierkot Grant/research support from: National Centre of Science - 2011/01/B/NZ5/05367, K. Bogunia-Kubik Grant/research support from: National Centre of Science - 2011/01/B/NZ5/05367, B. Nowak Grant/research support from: National Centre of Science - 2011/01/B/NZ5/05367, K. Białowąs: None Declared, L. Korman: None Declared, K. Gębura: None Declared, K. Kolossa: None Declared, S. Jeka: None Declared, P. Wiland: None Declared